Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jopy.12668
|View full text |Cite
|
Sign up to set email alerts
|

Narrative identity informs psychological adjustment: Considering three themes captured across five time points and two event valences

Abstract: Objectives How narrative identity and well‐being are intertwined as emerging adults process their lived experiences remains a critical theoretical and empirical question. We studied narrative identity among US emerging adults in a multiphase study. We aimed to test (1) if and how narrative identity themes (i.e., coherence, agency, growth) change rapidly across repeated narrations; (2) are related to reports of psychological adjustment (i.e., well‐being, recent stress) over time; and (3) whether the valence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 110 publications
1
14
0
Order By: Relevance
“…Overall, quantitative findings supported expectations that Black women's personality factors-here, hope as a facet of character and growth as a facet of narrative identity-would be positively associated with reports of well-being. We replicated existing work on the importance of character and narrative identity for well-being (Booker et al, 2021a(Booker et al, , 2021b(Booker et al, , 2021cMansfield et al, 2015;McLean et al, 2020) and the importance of positive life reasoning and meaning for Black, college-going women (Pals & McAdams, 2004;Wilkins, 2012). Hope and growth are each important for moving forward in life with independence and control-values that are important for the ways some Black women organize identity and value ideals of personal strength and dependability (Bradbury & Mashigo, 2018;Lewis, et al, 2013).…”
Section: Assessment Of Hypothesesmentioning
confidence: 72%
See 4 more Smart Citations
“…Overall, quantitative findings supported expectations that Black women's personality factors-here, hope as a facet of character and growth as a facet of narrative identity-would be positively associated with reports of well-being. We replicated existing work on the importance of character and narrative identity for well-being (Booker et al, 2021a(Booker et al, , 2021b(Booker et al, , 2021cMansfield et al, 2015;McLean et al, 2020) and the importance of positive life reasoning and meaning for Black, college-going women (Pals & McAdams, 2004;Wilkins, 2012). Hope and growth are each important for moving forward in life with independence and control-values that are important for the ways some Black women organize identity and value ideals of personal strength and dependability (Bradbury & Mashigo, 2018;Lewis, et al, 2013).…”
Section: Assessment Of Hypothesesmentioning
confidence: 72%
“…Mansfield et al (2015) found that personal growth in narratives about interpersonal conflicts of personal transgressions was related to increased well-being, selfcompassion, and forgiveness among college adults. Booker and colleagues (Booker, 2019;Booker et al, 2021aBooker et al, , 2021c found similar associations of growth from emerging adults' narratives of interpersonal conflict and personal setbacks. Further, Bauer and colleagues (Bauer & McAdam's, 2004Bauer, et al, 2005;Bauer & Park, 2010) showed that narrated growth is beneficial for well-being and remains relevant for adjustment throughout adulthood.…”
Section: Personality and Psychological Well-beingmentioning
confidence: 88%
See 3 more Smart Citations